Students' Preceptions and Attitudes Towards the Use of Instagram in English Language Writing - Ayesha Kusuma Aulia; Wilda Tatimatul Jahro; Zahra Maulida Aprianti; M. Alfian Ahsan; Nafan Tarihoran (LPPM Universitas Bina Bangsa, 2026)
This study aims to investigate students’ perceptions and attitudes toward the use of Instagram in English language writing. The research employed a descriptive quantitative design using a survey method. Data were collected through a structured questionnaire distributed via Google Forms to 100 university students from different semesters. The instrument consisted of 10 statements measured using a five-point Likert scale to examine writing frequency, confidence, motivation, and vocabulary development. The findings indicate that most students have positive perceptions of Instagram as a learning tool, as it encourages more frequent writing, enhances confidence, and allows students to express ideas more freely. Instagram also contributes to vocabulary improvement and increases students’ motivation through its interactive features, such as captions, comments, and direct messages. However, some students showed neutral responses regarding its effectiveness as a focused writing medium due to potential distractions from entertainment content. These findings suggest that Instagram can be used as a supportive tool in English writing instruction when integrated with appropriate guidance.